2012
DOI: 10.1029/2011jg001798
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the composition and lability of dissolved organic matter in Siberia's Kolyma River basin

Abstract: [1] High-latitude northern rivers export globally significant quantities of dissolved organic carbon (DOC) to the Arctic Ocean. Climate change, and its associated impacts on hydrology and potential mobilization of ancient organic matter from permafrost, is likely to modify the flux, composition, and thus biogeochemical cycling and fate of exported DOC in the Arctic. This study examined DOC concentration and the composition of dissolved organic matter (DOM) across the hydrograph in Siberia's Kolyma River, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
375
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(420 citation statements)
references
References 97 publications
38
375
7
Order By: Relevance
“…Despite this, we did not find evidence for widespread consistent and rapid in-stream and estuarine processing of fluvial C. C losses were confined to a few biogeochemical 'hot spots' in the lower reaches of the catchment and sporadic elsewhere, yet where they occurred the losses were on occasion very high, up to 44 % for DOC loss downstream of confluences and approximately 30 % DOC loss during estuarinefreshwater mixing. These results provide evidence that peat-derived fluvial C may be highly reactive, and that rapid physico-chemical processes may at times cause losses that are significantly larger than reported at longer timescales for microbial consumption (Dawson et al 2012;Hulatt et al 2014;Stutter et al 2013) or photochemical degradation (Mann et al 2012;Worrall and Moody 2014). The strong negative correlation between reach-scale declines in DOC/POC and Mg and Si suggest that on most occasions apparent fluvial C losses are due to mixing with unmeasured sub-surface inputs of mineral-rich and POCor DOC-poor waters, rather than in-stream processing.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Despite this, we did not find evidence for widespread consistent and rapid in-stream and estuarine processing of fluvial C. C losses were confined to a few biogeochemical 'hot spots' in the lower reaches of the catchment and sporadic elsewhere, yet where they occurred the losses were on occasion very high, up to 44 % for DOC loss downstream of confluences and approximately 30 % DOC loss during estuarinefreshwater mixing. These results provide evidence that peat-derived fluvial C may be highly reactive, and that rapid physico-chemical processes may at times cause losses that are significantly larger than reported at longer timescales for microbial consumption (Dawson et al 2012;Hulatt et al 2014;Stutter et al 2013) or photochemical degradation (Mann et al 2012;Worrall and Moody 2014). The strong negative correlation between reach-scale declines in DOC/POC and Mg and Si suggest that on most occasions apparent fluvial C losses are due to mixing with unmeasured sub-surface inputs of mineral-rich and POCor DOC-poor waters, rather than in-stream processing.…”
Section: Discussionmentioning
confidence: 64%
“…Wickland et al (2012) also found that the proportion of biodegradable DOC (%BDOC) was significantly related to DOC 'quality' as inferred by optical and fluorescence proxy measurements. In tributaries of the Kolyma basin that drains to the Arctic Ocean, Mann et al (2012) found that biological removal of DOC was strongly and positively correlated with fresh plant-derived C and ammonium (NH 4 ? -N) concentrations and negatively correlated with low molecular weight fulvic-like C, assumed to be a more degraded fraction of the DOC pool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Laptev Sea and the East Siberian Sea are surrounded and underlain by permafrost and are characterized by the degradation of coastal ice complex and terrestrial permafrost containing an extensive pool of ancient labile organic matter (OM) Sánchez-García et al, 2014;Schirrmeister et al, 2011;Tesi et al, 2014;Vonk et al, 2014). They are strongly impacted by the input and transformation of terrestrial OM Dudarev et al, 2006;Gustafsson et al, 2011;Mann et al, 2012Mann et al, , 2015Semiletov et al, 2007Semiletov et al, , 2016Tesi et al, 2016;Bröder et al, 2016;. The input of suspended as well as dissolved terrigenous material (Alling et al, 2010;Raymond et al, 2007;Holmes et al, 2012) including optically active fractions of dissolved OM, colored dissolved OM (CDOM; Pugach et al, , 2017, and the presence of ice cover throughout a significant part of the year reduces the depth of solar radiation penetration into the water column.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the Kolyma River in northeast Siberia has identified marked variation in annual discharge that is associated with large pulses of organic matter flux to the Arctic Ocean during spring freshet, providing detailed temporal characterization of DOM in the Kolyma River mainstem across the annual hydrograph (e.g., Mann et al, 2012). Furthermore, selective processing and loss of permafrostderived DOM has been shown to occur via microbial metabolism throughout the Kolyma River basin, as waters move downstream through the fluvial network (Mann et al, 2014Spencer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%